Stabilare materialflöde som grund för ökad produktionseffektivitet - Mohamad, Nader; Qiyam, Omid (My University, 2026)
Variations in material flow constitute a common challenge in industrial production systems and can lead to minor stoppages, reduced production rates, and inefficient utilization of existing capacity. This bachelor's thesis addresses issues related to uneven material flow in an industrial bagging process for powder-based material, where the actual production rate varies despite unchanged machine settings. The core message of the study is that variation in material flow, especially during the handling of the powder material, can limit the production rate even though the technical capacity of the packing line is higher. By improving the design of the material connection and working in a more standardized way during startup, the flow can be stabilized and the buffer level maintained more evenly. This can contribute to fewer minor stoppage, more stable production, and better utilization of the line’s capacity. For the company, this represents an opportunity to increase production efficiency and achieve more robust operations when handling different materials. The purpose of the study is to map the current state of the material flow, identify possible causes of flow variations and predictable production. The work has been conducted as a case study in an industrial production environment combining qualitative methods such as process observation and interviews with operating technicians with quantitative elements in the form of time studies and analysis of available production data. The analysis has been carried out using tools from Lean and Six Sigma, including the DMAIC structure and cause and effect analysis. The results show that variations in material flow can be linked to both technical factors in the transition between container and piping system as well as differences in routines and machine settings during start up and container changes. The study results in improvement proposals at a conceptual level such as adjustments to design solutions, standardization of machine settings, and improved data collection. These proposals aim to stabilize the material flow, reduce minor stoppages, and improve the utilization rate of the bagging machines capacity. The results are intended to serve as a design decision making basis for further technical and organizational actions within the production process.